A Checklist of Philippine Ferns - Salgado, Alfredo E. (1990)
A provisional checklist of Philippine fern taxa is provided. Thirty one families, 151 genera and 958 species are reported. An increase of 14 families , i genra and 15 species is recorded since the last inventory was made by Copeland (1961). The composition of the families follows closely bur not exactly of Flora Malesiana (Holtrum, 1959). Other differences from Copeland's inventory are the circumscription of genra, the addition of a substantial number of new species ans the updating of nomenclature.
Includes bibliographical references (pages 146-148)
Keywords: Botany; Philippine Ferns; Philippine plants